Entre casas, ruas e igrejas: crianças abandonadas na cidade da Paraíba oitocentista - Oliveira, Luiza Iolanda Pegado Cortez de (2014)
This study aims at analysing available information regarding exposed and orphaned infants in nineteenth century s Paraíba and by these means comprehending the responsibility mechanisms of the province s Holy House of Mercy (Santa Casa de Misericórdia) and Government regarding these children s custody and destination. Some specific objectives stem from the aforementioned general objective and are as follows: situate the Province of Paraíba in the context of growing planning policies for both the people and the city, supported by the ideas of hygienism and philanthropy; comprehend spiritual bonds formed between infants and godparents; study the roles destined to poor exposed and orphaned infants, particularly the ones related to work, for boys, and marriage, for girls. In order to proceed with the research, the following documents were used: reports by purveyors (provedores) and inspectors (mordomos) corresponding to the period from 1860 to 1889; Book of the Exposed (Livro dos Expostos), from 1869 to 1897; Baptism Records (Assentos de Batismo), from 1833 to 1860; reports by Province Presidents, from 1852 to 1889; data on the first census performed in Brazil, in 1872; and local newspapers issued in the nineteenth century. This particular choice of period is due to the transformations which took place in the Province of Paraíba in both hygienic order and city organization, turning it into a civilised place. During the development of the analysis, bibliography connected to Social History was used as resource to observe relations between Paraíba s Province Government posture towards abandoned children and Rio Grande do Norte and Pernambuco Provinces. Therefore, our endeavour was to discuss particular aspects of Paraíba s Government policies regarding abandoned children during the studied period.